Peran Literasi Digital Dalam Meningkatkan Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Siti Aysa Arni Wasarai; Asmida Asmida; Nur Azizah Safitri (Jurnal Sultra Elementary School, 2023)
Digital literacy plays an important role in developing critical thinking skills of elementary school students. With the advancement of information and communication technology, children are now more exposed to information coming from various online sources. Digital literacy which includes the ability to access, evaluate, and manage information can strengthen students' critical thinking skills. This study aims to examine the role of digital literacy in improving critical thinking skills of elementary school students through an in-depth literature study. The results of the study indicate that digital literacy can improve students' ability to analyze, evaluate, and utilize information effectively, which in turn strengthens their critical thinking skills.